Two pediatric patients with hemiplegic migraine presenting as acute encephalopathy: case reports and a literature review - Xiang, Yu; Li, Fei; Song, Zhenfeng; Yi, Zhi; Yang, Chengqing; Xue, Jiao; Zhang, Ying (Frontiers in Pediatrics, 2023)
Hemiplegic migraine (HM) is a rare subtype of migraine. The core symptoms of HM are headache and motor weakness. HM in children may be atypical in the initial stage of the disease, which could easily lead to misdiagnosis. We report two cases of atypical hemiplegic migraine that onset as an acute encephalopathy. The atypical clinical presentation of these two patients led to a challenging diagnosis.Both patients were eventually diagnosed with HM by whole-exome sequencing. The result of patient #1 showed a de novo mutation, c.674C>A (p. Pro225His), in exon 5 of the CACNA1A gene. The result of patient #2 showed a missense mutation (c.2143G>A, p. Gly715Arg) in exon 16 of the ATP1A2. Both of them were given prophylactic treatment after the encephalopathy symptoms resolved. When similar clinical cases appear, gene detection is particularly important, which is conducive to early diagnosis and treatment. Early recognition and treatment of the disease can help improve the prognosis.Blood samples (2 ml) were collected from patients and their parents. DNA was isolated from peripheral blood using a DNA Isolation Kit (Blood DNA Kit V2, CW2553). Concentrations were determined on a Qubit fluorometer (Invitrogen, Q33216) using a Qubit dsDNA HS Assay Kit (Invitrogen, Q32851). Agarose gel (1%) electrophoresis was performed for quality control. DNA libraries were prepared with a KAPA Library Preparation Kit (Kapa Biosystems, KR0453) following the manufacturer's instructions. Hybridization of pooled libraries to the capture probes (IDT xGen Exome Research Panel v1.0) and removal of nonhybridized library molecules was carried out according to the SeqCap Hybrid Mix System. Sample dilution, flow cell loading, and sequencing were performed according to the Illumina specifications. DNA libraries were sequenced on the Illumina NovaSeq platform as paired-end 200-bp reads.Sequence variants were annotated using population and literature databases, including 1000 Genomes,